Can baseline ML Flow test results predict leprosy reactions? An investigation in a cohort of patients enrolled in the uniform multidrug therapy clinical trial for leprosy patients in Brazil. Issue 1 (December 2016) - Hungria, Emerith; Oliveira, Regiane; Penna, Gerson; Aderaldo, Lúcio; Pontes, Maria; Cruz, Rossilene; Gonçalves, Heitor; Penna, Maria; Kerr, Ligia; Stefani, Mariane; Bührer-Sékula, Samira
Abstract Background The predictive value of the serology to detection of IgM against theMycobacterium leprae -derived phenolic glycolipid-I/PGL-I to identify leprosy patients who are at higher risk of developing reactions remains controversial. Whether baseline results of the ML Flow test can predict leprosy reactions was investigated among a cohort of patients enrolled in The Clinical Trial for Uniform Multidrug Therapy for Leprosy Patients in Brazil (U-MDT/CT-BR). Methods This was a descriptive study focusing on the main clinical manifestations of leprosy patients enrolled in the U-MDT/CT-BR from March 2007 to February 2012 at two Brazilian leprosy reference centers. For research purposes, 753 leprosy patients were categorized according to a modified Ridley-Jopling (R&J) classification and according to the development of leprosy reactions (reversal reaction/RR and erythema nodosum leprosum/ENL), and whether they had a positive or negative bacillary index/BI. Results More than half of the patients (55.5 %) reported leprosy reaction: 18.3 % (138/753) had a RR and 5.4 % (41/753) had ENL. Leprosy reactions were more frequent in the first year following diagnosis, as seen in 27 % (205/753) of patients, while 19 % (142/753) developed reactions during subsequent follow-up. Similar frequencies of leprosy reactions and other clinical manifestations were observed in paucibacillary (PB) and multibacillary (MB) leprosy patients treated with U-MDT and regular MDT (R-MDT) (P = 0.43 andP = 0.61, respectively). Compared with PB patients, leprosy reactions were significantly more frequent in MB patients with a high BI, and more patients developed RR than ENL. However, RR and neuritis were also reported in patients with a negative BI. At baseline, the highest rate of ML Flow positivity was observed in patients with a positive BI, especially those who developed ENL, followed by patients who had neuritis and RR. Among reaction-free patients, 81.9 % were ML Flow positive, however, the differences were not statistically significant compared to reactional patients (P = 0.45). Conclusions MB and PB patients treated with R-MDT and U-MDT showed similar frequencies of RR and other clinical manifestations. Positive ML Flow tests were associated with MB leprosy and BI positivity. However, ML Flow test results at baseline showed limited sensitivity and specificity for predicting the development of leprosy reactions.